PAYMENT SYSTEM DESIGN SWIMMING POOL EMPLOYEES HONOR LEBAK BULUS-JAKARTA - Hesti Sulistyowati; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2001)
Payment of employee salaries to the system here, the processing of data (such as absenteeism data entry) must be done carefully, so that administrative functions can be run well and reliable. Employee usage fee payment system is expected to not be too difficult in its use, so that what is expected writer can be reached.